1986
DOI: 10.1073/pnas.83.21.8343
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency hyperthermia with successive monitoring of its effects on tumors using NMR spectroscopy.

Abstract: Radiofrequency (rf) hyperthermia was generated on rat glioma inoculated s.c. in CD Fisher rats by applying the rf pulse using the surface coil in the NMR spectrometer, and the effect was monitored successively in the same spectrometer by measuring 31p NMR spectra and 'H NMR images. In the 31P NMR spectrum at the preirradiation stage, nucleoside triphosphate peaks and a phosphomonoester peak were high and a Pi peak was low. After a rf pulse at a power of 5 W was applied continuously for 60 min, the nucleoside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 10 publications
2
8
3
Order By: Relevance
“…At 24 h after PDT irradiation, the level E P-NTP/Pi ratios remained significantly reduced compared to all pre-treatment control levels. Inter- (Figure 6), followed by a gradual return to near pretreatment levels by [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] h, a finding which is in agreement with other investigators (Naruse et al, 1986b;Chopp et al, 1987Chopp et al, , 1990 (Ceckler et al, 1986;Hilf et al, 1987 (Gibson et al, 1990).…”
Section: Methodssupporting
confidence: 81%
“…At 24 h after PDT irradiation, the level E P-NTP/Pi ratios remained significantly reduced compared to all pre-treatment control levels. Inter- (Figure 6), followed by a gradual return to near pretreatment levels by [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] h, a finding which is in agreement with other investigators (Naruse et al, 1986b;Chopp et al, 1987Chopp et al, , 1990 (Ceckler et al, 1986;Hilf et al, 1987 (Gibson et al, 1990).…”
Section: Methodssupporting
confidence: 81%
“…In vivo 31 P NMR experiments show that HT produced an irreversible 40% decrease in NTP/P i at the end of HT whereas pH i and pH e showed reversible decreases by $0.2 pH units during HT. These changes in cellular energy status and pH in the 9L gliosarcoma model are smaller compared to that reported for sc-implanted RIF-1 tumours [5,12,13,15] perhaps because of differences in the two tumour models. Previous HT studies on sc-implanted C6 glioma (13) and perfused gliosarcoma cells (11) also showed small changes in tumour pH (0.2 units) as reported here.…”
Section: Discussioncontrasting
confidence: 72%
“…The use of the same MR spectrometer with its components for RF heating as well as to excite spins to perform MR data collection was first proposed by Naruse et al [13]. In their study, they delivered RF HT to a sc-implanted tumour model in rat by applying continuous RF power to a surface coil.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other potential hyperthermic particles are silver, iron, zinc and lanthanum nanoparticles [46]. Presently, colloidal gold particles are used in monitoring metabolic changes as bound with antibodies, lipids during cellular uptake and endocytosis [47,48]. Carbon nanotubes were reported in thermal ablation of malignant tissue with DNA encaged carbon nanotubes [49].…”
Section: Introductionmentioning
confidence: 99%